The Depiction of Malala’s Struggle for Gender Equality as Seen on He Named Me Malala Film - Dedi Efendi; Dodi Oktariza; Azmita Yakub (Jurnal Ilmiah Langue and Parole, 2020)
This research is analyzes about the struggle of Malala’s in He Named Me Malala film. The purposes of this research are to explain the great efforts of young girl named Malala for gender equality on education and politic and to explain the positive and negative impact after defying gender in equality in He Named Me Malala film. In analyzing the research, the writer uses feminism approach and some supporting theories. The method used in the research is descriptive qualitative. The data are formed in words, phrases and sentences. The data are analyzed through four procedures: identifying, classifying, analyzing, and making conclusions of the data. Result of this research are the writer found some great efforts of Malala’s struggle on gender equality on education and politic. The last, the writer found the positive impact of the Malala’s effort on education and politic. Malala has given chance for the other women to get education and the right of politic which is the basic right of human being as seen on He Named Me Malala film.